COMPARISON OF TRANSPORTATION COMPANY PERFORMANCES: PRE AND DURING CORONA VIRUS PANDEMIC - Pawitraj, Pingky; Hastuti, Rini Tri (International Journal of Application on Economics and Business, 2024)
The effect of the Corona virus pandemic on the global economy is very large with the International Monetary Fund (IMF) estimating a global economic contraction in 2020 will result in a very large recession after the second world war. With this continuation, Indonesia's economic growth experienced a contraction of 2.07% in 2020 and is expected to improve gradually in 2021. The transportation sector is the industrial sector that was most significantly effected during the pandemic. This sector is one of the industrial sectors that collapsed due to the Corona virus pandemic, where corporate performance experienced a serious effect. Financial performance measures the level of success of a corporate. This research examines differences in the financial performance of transportation companies during the Corona virus pandemic and compares it with the period before the pandemic.The research used data from 2018-2021, with a total number of 132 samples from 11 companies that met the criteria of purposive sampling. Current Ratio, Return on Assets, and Debt to Assets Ratio are proxies in this research where Microsoft Excel and SPSS version 27 were used as data processing tools. Descriptive statistics was the first step, continued by classical assumption test in the form of normality test, and ended with hypothesis testing using the Paired Sample t-test. The research results show no differences in Current Ratio, differences in Return on Assets, and no differences in Debt to Assets Ratio. The implication of this research is to provide insights for companies to plan strategies and reduce risks.